Photoluminescence, scintillation properties and trap states of La2Si2O7Ce single crystal. (18th July 2018) - Wan, Huanhuan; Wang, Yong; Zhuang, Lvchao; Huang, Shimin; Zhang, Zhijun; Xu, Zhan; Mao, Rihua; Feng, He; Zhao, Jingtai
Abstract: Single crystal of La2 Si2 O7 :Ce (LaPS:Ce) was successfully grown by floating zone method for the first time. The structure of as grown sample is confirmed to be monoclinic with space group P21 /c by x-ray diffraction and energy dispersive spectra. Its photoluminescence (PL) and scintillation properties of LaPS:Ce crystal were characterized through vacuum ultra-violet excitation and emission spectra, PL decay curve, x-ray excitation luminescence spectrum, γ -ray multi-channel spectrum and afterglow spectrum. Emission peaks of this material are around 3.5 eV and 3.3 eV, corresponding to the typical transition 5d → 4f of Ce 3+ . The PL decay time of LaPS:Ce is 29.3 ns. The light yield of the sample is determined to be about 5400 ph MeV −1 with a low afterglow level. The trap states in LaPS:Ce are also studied through the thermally stimulated luminescence measurement.